PENGARUH METODE EKSPERIMEN BERBASIS LINGKUNGAN SEKITAR TERHADAP HASIL BELAJAR IPA SISWA KELAS V SDN 35 DUMME KABUPATEN SINJAI - Sudarto; Achmad Shabir; A. Nursaiful (STKIP Subang, 2026)
This study is a pre-experimental study with a one-group pretest–posttest design. The aim is to determine the effect of using an environment-based experimental method on the learning outcomes of fifth-grade students at Dumme Elementary School 35, Sinjai Regency. The population in this study was all fifth-grade students at Dumme Elementary School 35, with a sample size of 23 students determined using a saturated sampling technique. Data collection was conducted through tests. The data obtained were analyzed using descriptive and inferential statistical analysis techniques. The results of the descriptive statistical analysis indicate that the average pretest score for students' science learning outcomes was in the moderate category. After implementing the environment-based experimental method, the average posttest score increased significantly and was in the very high category. Furthermore, the results of the inferential statistical analysis using a paired samples t-test showed: t = (35.376) > t (1.717) at a 5% significance level. These results indicate a significant difference between students' science learning outcomes before and after implementing the environment-based experimental method. Conclusion: The use of environmental-based experimental methods significantly improved science learning outcomes for fifth-grade students at Dumme Elementary School 35, Sinjai Regency.